The Effect of Capital Adequacy, Financing Risk, and Islamic Corporate Governance on Financial Performance with Islamic Social Reporting as an Intervening Variable - Indra, Yesifa Rahmadian; Pramudena, Sri Marti (Indonesian Journal of Business Analytics, 2024)
The purpose of this research is to examine and analyze the effect of capital adequacy, financing risk, and Islamic Corporate Governance on financial performance through disclosure of Islamic Social Reporting. The population of this research consists of fifteen Sharia Commercial Banks (IB) in Indonesia which are registered with the Financial Services Authority. The sample consists of ten IBs. This research used quantitative approach with panel data regression method and Sobel test on Eviews-13. The results show that capital adequacy has a positive effect on financial performance. Financing risk, Islamic Corporate Governance, and Islamic Social Reporting have no effect on financial performance. Islamic Social Reporting cannot mediate the capital adequacy, financing risk, and Islamic Corporate Governance on financial performance.